Employee Engagement as an Intervening Variable in the Relationship Between Work-Life Balance and Employee Retention in Indonesian Digital Startups - Indah Noviandari; Anggraeni Rahmasari; Nurul Imamah; Elly Yuniar Nitawati (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study examines the mediating role of employee engagement in the relationship between work-life balance and employee retention among digital startup employees in Surabaya, Indonesia. Using a quantitative associative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS), data were collected from 150 respondents working in various digital startups through purposive sampling. The research employed validated instruments measuring work-life balance, employee engagement, and employee retention using a 5-point Likert scale. Results demonstrate that work-life balance has a positive and significant direct effect on employee retention (β = 0.30, p < 0.001) and employee engagement (β = 0.50, p < 0.001). Employee engagement also significantly influences employee retention (β = 0.30, p < 0.001). Furthermore, employee engagement partially mediates the relationship between work-life balance and employee retention with an indirect effect of 0.15 (p = 0.002). The model explains 46.8% of the variance in employee retention and demonstrates adequate predictive relevance (Q² = 0.312). These findings indicate that while work-life balance directly contributes to employee retention, its effect is enhanced through increased employee engagement. The study contributes to human resource management literature by highlighting the importance of integrating work-life balance policies with engagement enhancement strategies in the dynamic startup environment. Practical implications suggest that digital startups should focus on creating flexible work arrangements while simultaneously fostering emotional and psychological attachment to improve talent retention in Indonesia's competitive tech sector.